Hungary : Financial Sector Assessment Program; Detailed Assessment of Standards and Codes - Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2005)
This paper presents an assessment of Hungary's antimoney laundering (AML) and combating the financing of terrorism measures. The Hungarian authorities have made significant progress in strengthening their AML regime. The most important step has been the passage of a revised AML Act of 2003, replacing the 2001 revision of the original 1994 AML Act. With this, the legislative framework for AML is in place, and has been extended to nonfinancial businesses and professions. Financial institutions' compliance with the AML requirements is well supervised, and they are well aware of their obligations under the Act.